Safety and Reliability - Safe Societies in a Changing World Proceedings of ESREL 2018, June 17-21, 2018, Trondheim, Norway - Barros, Anne; van Gulijk, Coen; Haugen, Stein; Erik Vinnem, Jan; Kongsvik, Trond (Taylor & Francis, 2018)
The contributions cover a wide range of methodologies and application areas for safety and reliability that contribute to safe societies in a changing world. These methodologies and applications include: - foundations of risk and reliability assessment and management - mathematical methods in reliability and safety - risk assessment - risk management - system reliability - uncertainty analysis - digitalization and big data - prognostics and system health management - occupational safety - accident and incident modeling - maintenance modeling and applications - simulation for safety and reliability analysis - dynamic risk and barrier management - organizational factors and safety culture - human factors and human reliability - resilience engineering - structural reliability - natural hazards - security - economic analysis in risk management